Is R2P a Legal Norm? : State Practice and Opinio Juris 2000-2022 - Naga, Dareen H. Aboul, (Human Rights and Humanitarian Law E-Books Online, Collection 2025., 2025)
Many ask if R2P is legally binding or not. By following the development of R2P from 2000-2022 and governments interactions with it throughout those years internationally, regionally and nationally, a perspective is given regarding its development as a norm within international law. The state practice and opinio juris of countries from different regions, representing varying perspectives, and the application of R2P throughout those years, provide the reader with insights on where R2P stands after more than 20 years of being part of the international fora. See Less